2022
DOI: 10.1021/acsami.2c10197
|View full text |Cite
|
Sign up to set email alerts
|

Low Dark Current Organic Photodetectors Utilizing Highly Cyanated Non-fullerene Acceptors

Abstract: Organic materials combining high electron affinity with strong absorption in the visible spectrum are of interest for photodetector applications. In this study, we report two such molecular semiconductors, based upon an acceptor–donor–acceptor (A-D-A) approach. Coupling of an acceptor end group, 2,1,3-benzothiadiazole-4,5,6-tricarbonitrile (TCNBT), with a donor cyclopentadithiophene core affords materials with a band gap of 1.5 eV and low-lying LUMO levels around −4.2 eV. Both materials were readily synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…With an average dark current J d at −2 V of 5.06 nA cm −2 , the PTQ10:(tb‐Ph) 2 ‐F 4 SiPc devices perform very similarly to previously reported PTQ10‐integrating OPDs with J d = 1.1 nA cm −2 for the system PTQ10:5,5′‐[(9,9‐Dioctyl‐9H‐fluorene‐2,7‐diyl)bis(2,1,3‐benzothiadiazole‐7,4‐diylmethylidyne)]bis[3‐ethyl‐2‐thioxo‐4‐thiazolidinone] (FBR) [ 62 ] and J d = 0.13 nA cm −2 for the system PTQ10:2‐ethylhexyl‐2,1,3‐benzo‐thiadiazole‐4,5,6‐tricarbonitrile (EH‐TCNBT). [ 63 ] At an average of 4.45 ∙ 10 12 Jones, PTQ10:(tb‐Ph) 2 ‐F 4 SiPc devices also displayed detectivity D * at a higher or the same order of magnitude as the comparable devices, [ 56,62,63 ] all of which were composed of high SC acceptors. [ 13 ] Figure S6 shows that PTQ10:(tb‐Ph) 2 ‐F 4 SiPc devices respond linearly with varying irradiance over five orders of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…With an average dark current J d at −2 V of 5.06 nA cm −2 , the PTQ10:(tb‐Ph) 2 ‐F 4 SiPc devices perform very similarly to previously reported PTQ10‐integrating OPDs with J d = 1.1 nA cm −2 for the system PTQ10:5,5′‐[(9,9‐Dioctyl‐9H‐fluorene‐2,7‐diyl)bis(2,1,3‐benzothiadiazole‐7,4‐diylmethylidyne)]bis[3‐ethyl‐2‐thioxo‐4‐thiazolidinone] (FBR) [ 62 ] and J d = 0.13 nA cm −2 for the system PTQ10:2‐ethylhexyl‐2,1,3‐benzo‐thiadiazole‐4,5,6‐tricarbonitrile (EH‐TCNBT). [ 63 ] At an average of 4.45 ∙ 10 12 Jones, PTQ10:(tb‐Ph) 2 ‐F 4 SiPc devices also displayed detectivity D * at a higher or the same order of magnitude as the comparable devices, [ 56,62,63 ] all of which were composed of high SC acceptors. [ 13 ] Figure S6 shows that PTQ10:(tb‐Ph) 2 ‐F 4 SiPc devices respond linearly with varying irradiance over five orders of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, in the development of materials, great attention is being paid to the development of n-type materials for replacing fullerene acceptors with organic small molecule acceptors (SMAs). However, since the bottleneck of SMA-based OPDs is the high J d values in the devices, many synthesis and device studies have focused on increasing D * via suppression of J d . , Huang et al reported a cyclopentadithiophene (CPDT)-based asymmetric SMA, which enables a “thick junction” to suppress J d in the devices, resulting in a promising OPD performance with a J d of 7.0 × 10 –9 A cm –2 , R of 0.45 A/W, and shot-noise-limited specific detectivity ( D sh *) of 3.31 × 10 13 Jones, under 940 nm illumination at −0.1 V . Lee et al.…”
Section: Introductionmentioning
confidence: 99%
“…27−35 However, since the bottleneck of SMA-based OPDs is the high J d values in the devices, many synthesis and device studies have focused on increasing D* via suppression of J d . 36,37 Huang et al reported a cyclopentadithiophene (CPDT)-based asymmetric SMA, which enables a "thick junction" to suppress J d in the devices, resulting in a promising OPD performance with a J d of 7.0 × 10 −9 A cm −2 , R of 0.45 A/ W, and shot-noise-limited specific detectivity (D sh *) of 3.31 × 10 13 Jones, under 940 nm illumination at −0.1 V. 38 Lee et al also reported several asymmetric SMAs, which were highly efficient in improving OPD performance (J d of 5.22 × 10 −8 A cm −2 , R of 0.37 A/W, and D* of 2.86 × 10 12 Jones) under a 1050 nm illumination at −0.5 V. 39 × 10 −8 A cm −2 , R of 0.5 A/W, and D sh * of over 10 12 Jones in the broadband of 380−940 nm at −0.5 V via a thermally induced antiaggregation evolution strategy. 40 Kim et al synthesized a simple nonfused ring SMA, which showed a high R of 0.39 A/W and D sh * of 1.27 × 10 13 Jones under a 800 nm illumination at −0.1 V by "thick junction".…”
Section: ■ Introductionmentioning
confidence: 99%